Comment - Sweezy, Paul M. (Quarterly Journal of Economics, 1972)
Journal Article Symposium: Economics of the New Left: Comment Get access Paul M. Sweezy Paul M. Sweezy Monthly Review Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 86, Issue 4, November 1972, Pages 658–664, https://doi.org/10.2307/1882049 Published: 01 November 1972